Colibactin‐positive Escherichia coli induce a procarcinogenic immune environment leading to immunotherapy resistance in colorectal cancer. Issue 11 (10th March 2020) - Lopès, Amélie; Billard, Elisabeth; Casse, Al Hassan; Villéger, Romain; Veziant, Julie; Roche, Gwenaëlle; Carrier, Guillaume; Sauvanet, Pierre; Briat, Arnaud; Pagès, Franck; Naimi, Souad; Pezet, Denis; et al.
Abstract : Colibactin‐producing E. coli (CoPEC) are frequently detected in colorectal cancer (CRC) and exhibit procarcinogenic properties. Because increasing evidence show the role of immune environment and especially of antitumor T‐cells in CRC development, we investigated the impact of CoPEC on these cells in human CRC and in the APC Min/+ mice colon. T‐cell density was evaluated by immunohistochemistry in human tumors known for their CoPEC status. APC min/+ mice were chronically infected with a CoPEC strain (11G5). Immune cells (neutrophils and T‐cell populations) were then quantified by immunofluorescent staining of the colon. The quantification of lymphoid populations was also performed in the mesenteric lymph nodes (MLNs). Here, we show that the colonization of CRC patients by CoPEC is associated with a decrease of tumor‐infiltrating T lymphocytes (CD3 + T‐cells). Similarly, we demonstrated, in mice, that CoPEC chronic infection decreases CD3 + and CD8 + T‐cells and increases colonic inflammation. In addition, we noticed a significant decrease in antitumor T‐cells in the MLNs of CoPEC‐infected mice compared to that of controls. Moreover, we show that CoPEC infection decreases the antimouse PD‐1 immunotherapy efficacy in MC38 tumor model. Our findings suggest that CoPEC could promote a procarcinogenic immune environment through impairment of antitumor T‐cell response, leading to tumoral resistance to immunotherapy. CoPEC could thus be a new biomarker predicting the anti‐PD‐1 response in CRC. Abstract : What's new? Among the bacteria frequently isolated from colorectal cancer (CRC) tissues, some species including Escherichia coli play a well‐established role in CRC development. However, in vivo mechanisms by which these bacteria promote colorectal carcinogenesis are not yet well elucidated. Here, the authors show that chronic infection by Colibactin‐producing E. coli (CoPEC) creates a specific inflammatory environment in the colon with a decrease in anti‐tumor T‐cells, which could be associated with the carcinogenic effect of colibactin and tumor resistance to immunotherapy. Finally, the results show that CoPEC could be a new biomarker to predict anti‐PD‐1 immunotherapy treatment response in CRC patients.